Fred H. Lawson. The Social Origins of Egyptian Expansionism during the Muhammad 'Ali Period. Nueva York: Columbia University Press, 1992. xiii-215 pp. - Taboada, Hernán G. H. (Estudios de Asia y África, 1994)
-